A survey of rift valley fever and associated risk factors among the one-humped camel (Camelus dromedaries) in Sudan. Issue 1 (December 2015) - Abdallah, Maiy; Adam, Ibrahim; Abdalla, Tamadur; Abdelaziz, Sanaa; Ahmed, Mohamed; Aradaib, Imadeldin
Abstract Background Rift valley fever (RVF) is a mosquito-borne viral disease of domestic livestock and wild ruminants. In camels RVF may cause abortion among pregnant camels, but is most often asymptomatic among other camels. In this study, a seroepidemiological survey was conducted to determine the prevalence of RVFV antibodies and to identify the potential risk factors associated with RVFV seropositivity among the Sudanese one-humped camel (Camelus dromedaries ) in Khartoum State, Sudan. A cross sectional study was conducted in Khartoum State, Sudan, in a total of 240 camels selected randomly from four localities. Sera sampled were tested for the presence of RVFV-specific immunoglobulin G (IgG) antibodies using a competitive enzyme-linked immunosorbent assay (c-ELISA). Results RVFV seropositivity was recorded in 23 out of 240 animals, prevalence rate of 9.6 % among camels in Khartoum State. Age (OR = 8.29, p -value = 0.04) and heavy rainfall (OR = 5.36, p value = 0.01) were recorded as potential risk factors for contracting RVF. Conclusions Older age and heavy rainfall were considered as potential risk factors for seropositivity to RVF. Surveillance for RVF among camels and distribution of mosquito vectors should continue to better understand the clinical signs associated with RVFV infection in camels and provide public health authorities an opportunity to anticipate and prepare for a possible RVF outbreak in Khartoum State, Sudan.